Pengaruh Model Pembelajaran Flipped Classroom Terhadap Kemandirian dan Hasil Belajar Siswa - Dewi Fatimah; Sri Kantun; Dwi Herllindawati (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
This study aims to determine the effect of the flipped classroom learning model on the independence and learning outcomes of class X students of the accounting skills program at Vocasional High School 1 Lumajang with a case study on the basic competencies of basic accounting equations for the 2022/2023 school year. This research is an experimental research with the type of research Pre-Experimental Design and using the One Group Pretest-Posttest research design. Methods of data collection using questionnaires, tests, interviews and documentation. The data analysis method used is the paired sample t-test. The results showed that the flipped classroom learning model had an effect on student learning independence with a Sig. 0.00 <0.05 and has an effect on learning outcomes with a Sig value. 0.03 <0.05. The results of the Percent N-Gain test show that the flipped classroom learning model has an effect on learning independence by 57% and on learning outcomes by 22%.